Implementation of Mindfulness in 66-years-old Female with Diabetic Post Surgery: A Case Report to Inform Nursing Role to Deliver Holistic Care - Ida Widaningsih; Titis Kurniawan; Kusman Ibrahim; Nursiswati Nursiswati (Indonesian Journal of Global Health Research, 2024)
Currently, there are no suggested psychological interventions or outcomes in the diabetic management guidelines. This case report presents the management of a 66-year-old female patient, Mrs. R, with diabetes mellitus, hypertension, and gastroesophageal reflux disease (GERD) who underwent exploratory laparotomy for retained stone exploration in the common bile duct (CBD). This Case report aimed to explore the implementation of mindfulness in patients post-operative. The patient experienced significant hyperglycemia, with blood glucose levels peaking at 436 mm Hg. Psychological assessment revealed a severe anxiety score of 31, which likely contributed to her unstable glycemic control. Throughout her unstable glycemic control. Throughout her severe condition, the patient was managed with total parenteral nutrition (TPN) due to fasting and green gastric contents, as part of the nursing intervention. Comprehensive nursing interventions, including regular blood glucose monitoring, insulin administration, and psychological support were employed. Mindfulness techniques such as guided meditation and breathing exercises have been introduced to alleviate hospital-induced distress and manage blood glucose levels. Following these interventions, her blood glucose level decreased to 167 mmHg, and the patient reported feeling calmer and more spiritually connected (Hamilton Rating Scale/ HARS 18). This case describes the management of post-surgical diabetic patients, highlighting the benefits of integrating psychological interventions to improve glycemic control and overall patient outcomes. Therefore, psychological interventions, particularly mindfulness, are needed for integration in diabetes management, especially in hospitals.